UJI KOMPARATIF PENDAPATAN USAHATANI JAGUNG LAHAN SAWAH DI KECAMATAN UTAN DAN KECAMATAN ALAS BARAT - Mahadisa Ade Rahman (Pusat Riset dan Publikasi, 2025)
This study aims to examine the differences in income levels of rice field corn farming businesses in Utan Sub District and Alas Barat Sub District. The determination of the research location was carried out purposively (intentionally) in Alas Barat Sub District and Utan Sub District based on the fact that these two districts are the districts with the largest corn harvests planted in rice fields. The number of samples in this study was 70 corn farmers who were taken accidentally, where 35 people were taken from each sub-district to be used as research respondents. Data collection in this study used structured interview techniques using interview guidelines prepared by the researcher. The data analysis technique in this study used a comparative test by comparatively examining the income of rice field corn farmers in Utan Sub District and Alas Barat Sub District based on the Fisher formula. The results of this study indicate that there was a significant difference in the income levels of corn farmers in Alas Barat Sub District and Utan Sub District. The main factor causing this difference was the scale of land area. The area of ??corn production land in Utan Sub District was larger than the area of ??corn production land in Alas Barat Sub District, so that the production results and income of corn farming in Utan Sub District are higher than the production results and income of corn farming in Alas Barat Sub District.